Wind-evoked anemotropism affects the morphology and mechanical properties of Arabidopsis. (18th November 2020) - Zhdanov, Oleksandr; Blatt, Michael R; Zare-Behtash, Hossein; Busse, Angela
Abstract : Arabidopsis thaliana adapts to wind through alterations in morphology, mechanical properties, and tissue organization, and exhibits positive anemotropism. The observed response differs from previously reported changes induced by mechanical perturbations. Abstract: Plants are known to exhibit a thigmomorphogenetic response to mechanical stimuli by altering their morphology and mechanical properties. Wind is widely perceived as mechanical stress and in many experiments its influence is simulated by applying mechanical perturbations. However, it is known that wind-induced effects on plants can differ and at times occur even in the opposite direction compared with those induced by mechanical perturbations. In the present study, the long-term response of Arabidopsis thaliana to a constant unidirectional wind was investigated. We found that exposure to wind resulted in a positive anemotropic response and in significant alterations to Arabidopsis morphology, mechanical properties, and anatomical tissue organization that were associated with the plant's strategy of acclimation to a windy environment. Overall, the observed response of Arabidopsis to wind differs significantly from previously reported responses of Arabidopsis to mechanical perturbations. The presented results suggest that the response of Arabidopsis is sensitive to the type of mechanical stimulus applied, and that it is not always straightforward to simulate one type of perturbation by another.